Dance-writing pandemic corpographies (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This paper analyzes the research group’s actions Writing/Inscrebed by/in the Body (Corpographies) of the Dance-Degree Course at the Federal University of Santa Maria (UFSM) in the pandemic context. Initially, the group suspended activities, but, later, returned online, changing the research scope to learning-teaching dance methods. The group’s members started to investigate ways to move and live/survive during the pandemic. The research used sensitive practices, based on somatic approaches. The text reflects on this process and how important it was for a healing movement, from leaving stupor to the know-feel. We conclude that the practices have an aesthetic and political character and the research is a sharing of the sensitivity.
Keywords: Dance; Pandemic; Sensitive practices